Sodium-23 MRI of whole spine at 3 Tesla using a 5-channel receive-only phased-array and a whole-body transmit resonator - Malzacher, Matthias; Kalayciyan, Raffi; Konstandin, Simon; Haneder, Stefan; Schad, Lothar R. (Zeitschrift für medizinische Physik, 2016)
Sodium magnetic resonance imaging (23Na MRI) is a unique and non-invasive imaging technique which provides important information on cellular level about the tissue of the human body. Several applications for 23Na MRI were investigated with regard to the examination of the tissue viability and functionality for example in the brain, the heart or the breast. The 23Na MRI technique can also be integrated as a potential monitoring instrument after radiotherapy or chemotherapy. The main contribution in this work was the adaptation of 23Na MRI for spine imaging, which can provide essential information on the integrity of the intervertebral disks with respect to the early detection of disk degeneration. In this work, a transmit-only receive-only dual resonator system was designed and developed to cover the whole human spine using 23Na MRI and increase the receive sensitivity. The resonator system consisted of an already presented 23Na whole-body resonator and a newly developed 5-channel receive-only phased-array. The resonator system was first validated using bench top and phantom measurements. A threefold SNR improvement at the depth of the spine (∼7cm) over the whole-body resonator was achieved using the spine array. 23Na MR measurements of the human spine using the transmit-only receive-only resonator system were performed on a healthy volunteer within an acquisition time of 10minutes. A density adapted 3D radial sequence was chosen with 6mm isotropic resolution, 49ms repetition time and a short echo time of 540μs. Furthermore, it was possible to quantify the tissue sodium concentration in the intervertebral discs in the lumbar region (120ms repetition time) using this setup.
Gesehen am 12.02.2019
Available online 17 April 2015